Exploring young learners' engagement with models as a written corrective technique in EFL and CLIL settings. (December 2020) - Coyle, Yvette; Roca de Larios, Julio
Abstract: This study explores written corrective feedback processing and uptake with two groups of young learners during a multi-stage writing task using model texts. Eight pairs of 9-to-11-year-olds from different instructional settings in primary education, an EFL class and a CLIL class, were required to write a narrative picture story, compare their drafts with feedback provided in the form of models and rewrite their original texts. The children's collaborative dialogue protocols and written notes were examined for evidence of the cognitive strategies they used to process the feedback upon noticing a mismatch between the models and their own output. Four strategies were identified in the data, although differences were observed in the extent and nature of their deployment by pairs from each setting, and in their impact on the children's uptake. While all pairs relied on the identification of surface differences between the model and their own draft, only the CLIL pairs paid attention to new and alternative features in the feedback. Evidence of uptake following unreported noticing was also found in the children's written texts. This study furthers our understanding of how young L2 learners engage with models and highlights the need to consider contextual variables in studies of feedback. Highlights: Young language learners activate a range of cognitive strategies when processing feedback in the form of model texts. Noticing of surface-level differences was the most widely-used feedback processing strategy by all pairs. Only CLIL pairs paid attention to alternative ideas and forms of expression in the models. Unreported noticing also led to uptake.